Design and Control of Diesel and Natural Gas Engines for Industrial and Rail Transportation Applications 2003
DOI: 10.1115/icef2003-0752
|View full text |Cite
|
Sign up to set email alerts
|

Study of Fuel Temperature Effects on Fuel Injection, Combustion and Emissions of Direct-Injection Diesel Engines

Abstract: The influence of inlet liquid fuel temperature on direct-injection diesel engines can be noticeable and significant. The work in this paper investigates the effects of inlet fuel temperature on fuel injection, in-cylinder combustion, and performance and emissions of medium-speed diesel engines. An enhanced understanding and simplified modeling of the variations in main fuel injection parameters affected by inlet fuel temperature are developed. The study indicates that the main affected injection parameters inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…When the ethanol fuel temperature is increased from 50°C to 90°C, the density of the ethanol fuel decreases from 763 to 721 kg/m 3 , viscosity decreases from 0.676 to 0.374 mPa s, and surface tension decreases from 0.0202 to 0.0152 N/m [34]. Experiments and simulations on the fuel injection process showed that, when the fuel temperature was increased, the actual injection timing was retarded, the peak rail pressure was decreased and the injection duration was prolonged [32,35]. The fuel mass flow rate was decreased with the increase of fuel temperature because of the decreased fuel density [24,36,37].…”
Section: Combustion Characteristics With Edi Heating At the Original mentioning
confidence: 99%
“…When the ethanol fuel temperature is increased from 50°C to 90°C, the density of the ethanol fuel decreases from 763 to 721 kg/m 3 , viscosity decreases from 0.676 to 0.374 mPa s, and surface tension decreases from 0.0202 to 0.0152 N/m [34]. Experiments and simulations on the fuel injection process showed that, when the fuel temperature was increased, the actual injection timing was retarded, the peak rail pressure was decreased and the injection duration was prolonged [32,35]. The fuel mass flow rate was decreased with the increase of fuel temperature because of the decreased fuel density [24,36,37].…”
Section: Combustion Characteristics With Edi Heating At the Original mentioning
confidence: 99%
“…In the mechanical injection system, the bulk modulus of fuels, mainly controlled by environmental temperature, 53 tends to affect the injection timing and thus the NOx emissions. 54,55 For a common-rail injection system, the change of compressibility derived from the speed of sound and the bulk modulus of blend fuels does not influence the injection timing. 51,56 Neither diesel nor PODE has C−C double bonds in the molecule structure, but the cetane number of diesel/ biodiesel/PODE blend fuels is obviously higher than that of D100.…”
Section: Engine Emissions Of Blend Fuelsmentioning
confidence: 99%
“…In this study, three types of nozzle with d h = 0.31 mm, 0.35 mm, and 0.4 mm, respectively were used. Further, since the fuel temperature shows marked effects on the fuel injection process [14], the DME inlet temperature was stabilized to 30°C, and this will be discussed further in this paper.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…It has been proved that the fuel injection parameters have shown pronounced effects on the fuel injection process and the engine combustion characteristics [10][11][12][13][14]. However, there have been few reports in the literature concerning the DME injection process.…”
Section: Introductionmentioning
confidence: 99%